TREATMENT OF MIDDLE EAR ATELECTASIS WITH SULPHURHEXAFLUORIDE - AN ALTERNATIVE METHOD - YALCIN, S; GOK, U; INAN, E; OZTURK, A; ASKIN, Z; HANCER, A (Multi-Science Publishing Co Ltd, 1993)
[Abstract Not Available]
XV World Congress of Otorhinolaryngology Head and Neck Surgery (ISTANBUL 93) -- JUN 20-25, 1993 -- ISTANBUL, TURKEY
Keywords: MIDDLE EAR ATELECTASIS; SULPHURHEXAFLUORIDE